Incorporating Values into the English Classroom - Odilia Ramírez Contreras (Asociación Colombiana de Profesores de Ingles, 2007)
This paper intends to report a study in which the teacher illustrates the way to incorporate values into the English as a Foreign Language (EFL) class. It highlights the important role teachers play in the education of new generations nowadays. It states that language forms can be used to contribute to the fostering of values in a given society when they are taught in a learner-centered curriculum approach as well as with a cross-curriculum view. Examples of the activities teachers can carry out to achieve this goal are taken from the experience that the author has had in her teaching in public schools.